Pandoro and Gen Z: Narration and Perception of Christmas Consumption on TikTok Platform by Visual Sociology - Massimiliano Moschin (Gastronomy)
Drawing upon the TikTok platform, this study analyzes the media consumption of content dedicated to “Pandoro,” a typical sweet from Verona, Italy, identifying the most successful categories through a visual sociology approach. It then sets out to obtain a deeper understanding of the conceptualization of the sweet and the narration of Pandoro consumption among Gen Z, focusing on a small group of students in the city of Verona itself and verifying how elements of conservatism, traditionalism, and passivity emerge in the realization of content. What also appears interesting is the confirmation, which emerged from TikTok, that Pandoro is seen as an Italian symbol rather than a typical food associated with the city of Verona.